Issues of transport sector improvement in the context of connected vehicles development - D. V. Kapski; S. V. Bogdanovich; P. V. Kurenkov; N. A. Filippova (Интеллект. Инновации. Инвестиции, 2024)
The article examines topical issues of improving the transportation industry in the context of the active development and implementation of connected vehicles (CVs). The relevance of the topic is driven by the rapid growth in the number of CVs, their increasing impact on the transportation system, and the need for a comprehensive optimization of the industry to fully realize the potential of new technologies.